A Novel Mutation in the VPS13B Gene in a Cohen Syndrome Patient with Positive Antiphospholipid Antibodies - Roghayeh Dehghan; Mahdiyeh Behnam; Alireza Moafi; Mansoor Salehi (Case Reports in Immunology)
Cohen syndrome is an autosomal recessive disorder with the primary symptoms of mental deficiency, progressive retinopathy, hypotonia, microcephaly, obesity of midchildhood onset, intermittent neutropenia, and dysmorphic facial features. The syndrome has high phenotypic heterogeneity and is caused by loss-of-function mutations in the VPS13B gene. Here, we introduce a novel homozygous nonsense mutation (c.8698G > T, p.E2900X) in the VPS13B gene in an 11-year-old Iranian boy with major symptoms of Cohen syndrome. He also had mild anemia accompanied by positive antiphospholipid antibodies, the latter has never been previously reported in Cohen syndrome.